Effect of Photothermal Therapy Using Gold Nanoparticles Conjugated with Hyaluronic Acid in an Intracranial Murine Glioblastoma Model - Domingo-Diez J; Foti A; Casanova-Carvajal Ó; Marrodán L; Granado N; Satriano C; Martínez-Murillo R; Serrano-Olmedo JJ; Ramos-Gómez M (International Journal of Nanomedicine)
Javier Domingo-Diez,1 Alice Foti,2 Óscar Casanova-Carvajal,1,3 Lorena Marrodán,1 Noelia Granado,4 Cristina Satriano,2 Ricardo Martínez-Murillo,4 José-Javier Serrano-Olmedo,1,5,6 Milagros Ramos-Gómez1,5,6 1Center for Biomedical Technology (CTB), Universidad Politécnica de Madrid (UPM), Madrid, 28223, Spain; 2Nano Hybrid Biointerfaces Laboratory (NHBIL), Department of Chemical Sciences, University of Catania, Catania, 95125, Italy; 3Departamento de Ingeniería Eléctrica, Electrónica, Automática y Física Aplicada, Escuela Técnica Superior de Ingeniería y Diseño Industrial ETSIDI, Universidad Politécnica de Madrid, Madrid, 28040, Spain; 4Neurovascular Research Group, Department of Translational Neuroscience, Instituto Cajal, CSIC, Madrid, 28002, Spain; 5Centro de Investigación Biomédica en Red para Bioingeniería, Biomateriales y Nanomedicina, Instituto de Salud Carlos III, Madrid, 28029, Spain; 6Departamento de Tecnología Fotónica y Bioingeniería, ETSI Telecomunicaciones, Universidad Politécnica de Madrid, Madrid, 28040, SpainCorrespondence: Milagros Ramos-Gómez, Universidad Politécnica de Madrid (UPM), Madrid, 28223, Spain, Email milagros.ramos@ctb.upm.esPurpose: Glioblastoma multiforme (GBM) is the most common and aggressive malignant brain tumor. Conventional treatments for GBM include surgery, chemotherapy, radiotherapy, or a combination of these. However, emerging therapies, such as hyperthermia treatments, are being developed. One of these new therapies is nanoparticle-mediated photothermal therapy (PTT), a non-invasive treatment that converts light into heat using photoagents such as plasmonic nanoparticles. High molecular weight hyaluronic acid (HA) has been described as a potential inhibitor of tumor progression and exhibits a high affinity for the CD44 receptor, which is present in GBM cells. The in vivo efficacy of gold nanorods (GNRs) biofunctionalized with HA-700kDa in PTT has been evaluated in a murine GBM model.Animals and Methods: Adult male C57/BL-6 mice (N=15), 3– 8-month-old, were used for PTT experiments. CT2A cells were injected into the mouse brain to establish a GBM model. Tumor-bearing mice were randomly divided into three groups: Control (untreated, n=5), GNRs (injected with GNRs, n=5) and PTT-treated (injected with GNRs and treated with laser, n=5). After GNR injection, mice were irradiated with a laser at 0.98 A (250mW) for 25 min over three consecutive days.Results: As observed in the analysis of tumor sizes from all MR images, animals treated with a laser following GNR injection exhibited significantly smaller tumor sizes compared to control and GNR-treated animals one week after the treatment. In addition, PTT treatment led to a notable improvement in the exploratory behavior of the treated animals and an increase in their life expectancy compared to untreated control mice.Conclusion: This study demonstrates the efficacy of GNR-based-PTT, applied to an orthotopic tumor model, using GNRs biofunctionalized with HA to target GBM CT2A cells. The treatment resulted in a reduction in tumor mass and an extension of life expectancy in GNR-PTT treated mice.Keywords: Gold nanorods, photothermal therapy, glioblastoma, murine tumor model